Contribuições da formação continuada para a prática pedagógica do professor de Educação Física - Silva, Ana Paula Vasconcelos da (2016)
This research aimed to organize and develop with teachers of Physical Education of the State of Mato Grosso a proposal for continuing education or continued formation, thus presenting alternatives to improve their pedagogical practices at school. Specifically: to identify the main difficulties related to teaching practice reported by Physical Education teachers working in public schools in the State of Mato Grosso; and identify the needs of physical education teachers regarding continued formation. The methodology follows a qualitative approach, descriptive and type of action- research. The sample has seven physical education teachers who work in the State of Mato Grosso, contractors or effective, crowded in the municipality of Barra do Garças. They were held 13 meetings with teachers from February to June 2015, with the proposal to discuss their practice. Data collection equipment used for photographic documentation, video and audio of the meetings, and also notes the field notebook. The results point to a satisfaction of teachers with regard to the development of training activities proposed. Among the difficulties presented by the teachers during the meetings highlighted the lack of equipment and physical infrastructure in some schools, the lack of interest of students in classes, the absence of an annual curriculum planning to be followed, and the difficulty in working some specific content such as dance, sports adventures, wrestling and capoeira. About their training needs teachers pointed to the importance of developing training sessions on more specific knowledge of Physical Education and connected to their reality with studies of its practices, difficulties and planning. This training process with the PE teachers showed that continuing education that puts the teacher at the center of the process and their practice as a guideline for discussions has more success and effectiveness for the teacher. The difficulty and teachers' needs are directly related to their practice and must be considered when planning the practical continued formation of Physical Education teachers.